Satellite remote sensing of deforestation in the Sungai Buloh Forest Reserve, Peninsular Malaysia - Jusoff, Kamaruzaman; Abdul Manaf, Mohd Rasol (Taylor & Francis, 1995)
Deforestation has been a very critical environmental problem during the past few decades. Monitoring the Earth's surface conditions and their changes are essential to the management of this global environmental problem. Remote sensing can provide an effective 1001 for monitoring environmental changes on a global scale. This has focused attention on developing more effective and efficient techniques for the management and survey of forest areas. This study was designed to assess the feasibility of utilizing Landsat TM data in monitoring deforestation in the Sungai Buloh Forest Reserve. Detection of land cover change due to urbanization was performed using rnulti-tempora! data taken in 1988and 1991. An IDRISI image processing system was used to analyse the satellite data. Multi-temporal images were registered and spectral signatures of each point were directly compared. Correlation analysis was used to evaluate the similarity of two spectral signatures. A false colour composite image of bands 4, 5 and 3 (Red-Green-Blue) was used in unsupervised classification. For detection of land cover change, both multi-temporal images were overlaid and the area was calculated. The study revealed that the rate of deforestation in the Sungai Buloh Forest Reserve is about 182ha yr with an accuracy of 90·0 per cent.